Comparative techno-economic and life cycle assessment of ammonia co-firing with different ammonia production routes in a 1100 MWe ultra-supercritical CFB coal power plant - Jae-Beom Lee; Jae-Hoon Jeon; Gwon-Woo Lee; Jin-Young Kim; Hye-Rin Kim; Eun-Uk Yu; Sung-Jin Pak; Sang-Jun Han; Shaukat Ali Mazari; Tae-Young Mun; Jong-Ho Moon (Fuel, 2027)

Scalable hybrid electrode-based capacitive deionization modules for practical water softening - Sang Baek Kim; Gun Jang; Wonji Jung; Hye Rin Park; Youngkyu Cho; Sung Pil Hong; Jee Yeon Kim; Changhoon Oh; Ho Seok Park (Water Research, 2026)

Physicochemical insights into ammonia-amine blending for CO2 capture: Speciation, ammonia volatilization, salt precipitation, and regeneration energy in aqueous NH3-MEA and NH3-AMP solutions - Sang-Jun Han; Hye-Rin Kim; Jin-Young Kim; Jae-Beom Lee; Gwon-Woo Lee; Jae-Hoon Jeon; Shaukat Ali Mazari; Ung Lee; Jong-Ho Moon (Chemical Engineering Journal, 2026)

Unravelling the Population Genetic Dynamics of the Ivory Snail (Babylonia areolata) in Vietnam: Guiding Sustainable Aquaculture Development - Sang Van Vu; Angkasa Putra; Sarifah Aini; Imon Abedin; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Thanh Tat Le; Hoang Huy Nguyen; Hien Van Doan; In Van Vu; Hyun-Woo Kim; et al. (Thalassas: An International Journal of Marine Sciences, 2026)

Genetic diversity and genome-wide association study of horticultural traits in pumpkins (Cucurbita moschata) originating from East Asia - Eun Su Lee; Yoon Jeong Jang; Ye-Rin Lee; Oakjin Lee; Hee-Bum Yang; Hye-Eun Lee; Koeun Han; Do-Sun Kim (Horticulture, Environment, and Biotechnology, 2026)

Cascade energy alignment and absorption enhancement via a guest donor strategy for efficient ternary organic solar cells - Ha Rin Kim; Jinwoong Hong; Donghwan Yun; Hyeseon Shin; Mihyun Kim; Youngchae Cho; Seungmin Baek; Gwangyong Shin; Guanchao Chen; Seyeong Song; Seonghun Lee; Tae Joo Shin; et al. (Chemical Engineering Journal, 2026)

Mitogenomic Characterization and Phylogenetic Insights of the Ornamental Sail-Fin Molly (Poecilia velifera) in Non-Native Indonesian Waters - Sarifah Aini; Rina; Sinar Pagi Sektiana; Soo Rin Lee; Ah Ran Kim; Hye-Eun Kang; Muhammad Hilman Fu’adil Amin; Won-Kyo Jung; Angkasa Putra; I Nyoman Suyasa; Shantanu Kundu; Hyun-Woo Kim (Biochemical Genetics, 2026)

Human adipose-derived stem cell exosomes alleviate human respiratory system-related cells damaged by exposure to SO2 derivatives - Ji-Seon Lee; You-Rin Kim; Dogeon Yoon; Ji Hye Park; Ga Eun You; Wook Chun (Journal of Biosciences, 2025)

Precision-controlled synthesis of monodisperse starch nanoparticles: Factors affecting the self-assembly kinetics - Hazzel Joy Adra; Da-hee Lim; Hye-rin Kim; Ki-baek Jeong; Ke Luo; Young-Rok Kim (Food Hydrocolloids, 2024)

Identification of the endangered species Haplotropis brunneriana (Insecta: Orthoptera) from South Korea using exuviae - Mannyun Kim; Hye-Rin Lee; Jong Eun Lee; Deokjea Cha (Journal of Insect Conservation, 2024)
Most Pamphagidae species are at risk of being endangered due to their flightlessness, low mobility, and small habitat range. For the same reason, Haplotropis brunneriana (Orthoptera: Pamphagidae) has been designated an endangered species in South Korea. Endangered species with small populations are difficult to observe and investigate because any damage or disturbance to them are prohibited. To address these problems, we first performed non-invasive genomic DNA (gDNA) extraction using exuviae to identify H. brunneriana . Second, we tested the limit of detection of gDNA in the exuviae and how long it could persist when exposed to artificial environmental conditions. Using exuviae, we identified cytochrome b as a species-specific marker of H . brunneriana that could distinguish them from other grasshoppers with sufficient specificity. In the limit of detection test, gDNA could persist and be amplified from exuviae for up to 40 days. Our results demonstrated that fewer than 10 days is recommended for amplifying gDNA from exuviae to obtain reproducible results. In conclusion, this non-invasive identification method using exuviae can be used as an alternative to species identification when it is difficult to find H. brunneriana in the habitat and has the advantage of allowing genetic research to be conducted without harming the endangered species.

Enzymatic characterization of sucrose phosphorylase from Bifidobacterium dentium: The initial enzyme in the cascade reaction - Hye-Rin Lee; Ye-Jin Kim; Chang-Young Lee; Sang Gil Lee; Tae Gyu Nam; Cheon-Seok Park; Dong-Ho Seo (Food Bioscience, 2024)

Multi-functional energy conversion by strongly coupled Ag3PO4/ZIF-67 heterostructures - Harshavardhan Mohan; Sethumathavan Vadivel; Suhwan Yoo; Ga Hyeon Ha; Gitae Kim; Hye Rin Lee; Han-Kyu Choi; Taeho Shin (Journal of Environmental Chemical Engineering, 2024)

Cobalt–molybdenum–selenide nanoflowers for bifunctional visible light photocatalysis - Harshavardhan Mohan; Ga Hyeon Ha; Gitae Kim; Hye Rin Lee; Hakju Lee; Kyoungsoo Kim; Taeho Shin (Chemosphere, 2023)

The Relationship between the Drug Delivery Properties of a Formulation of Teriparatide Microneedles and the Pharmacokinetic Evaluation of Teriparatide Administration in Rats - Yu-Jeong Oh; Nae-Won Kang; Hye-Rin Jeong; Seo-Yeon Sohn; Yae-Eun Jeon; Na-Young Yu; Yura Hwang; Sunkyung Kim; Dae-Duk Kim; Jung-Hwan Park (Pharmaceutical Research, 2022)

Efficacy of a bleomycin microneedle patch for the treatment of warts - Ha Ryeong Ryu; Hye-Rin Jeong; Hye-Seung Seon-Woo; Jung Soo Kim; Seul Ki Lee; Hee Joo Kim; Jin Ok Baek; Jung-Hwan Park; Joo Young Roh (Drug Delivery and Translational Research, 2018)

Mutational analysis of BRAF and K-ras in gastric cancers: absence of BRAF mutations in gastric cancers - Il-Jin Kim; Jae-Hyun Park; Hio Chung Kang; Yong Shin; Hye-Won Park; Hye-Rin Park; Ja-Lok Ku; Seok-Byung Lim; Jae-Gahb Park (Human Genetics, 2003)